Response to DDAVP in children with von Willebrand disease type 2 - Schneppenheim, R.; Budde, U.; Beutel, K.; Hassenpflug, W.-A.; Hauch, H.; Obser, T.; Oyen, F.; Schneppenheim, S.; Schrum, J. (Hämostaseologie, 2009)
We have prospectively evaluated the biologic response to desmopressin (DDAVP) in 28 children with type 2 von Willebrand disease (VWD) in correlation with the phenotype and the molecular defect of VWF. The diagnosis of VWD type 2 was mainly based on VWF functional parameters and/or an aberrant VWF multimer pattern. Seventeen different mutations were identified (6 of them novel). No response with respect to the functional parameters VWF:RCo and/or VWF:CB was seen in patients with severe abnormality of the VWF multimer pattern. One patient with VWD type 2A phenotype IIC Miami did not respond with respect to VWF:CB, but showed a good response of VWF:Ag and FVIII:C as expected. Interestingly he showed a persistently high level of VWF:Ag and FVIII:C up to 4 hours after DDAVP infusion. Patients with minor alterations of multimer structure and particular mutations responded well to DDAVP, whereas patients with normal multimer structure but a defect in platelet dependent functional parameters did not respond with VWF:RCo. Conclusion: Children with VWD type 2 show a variable response to desmopressin depending on the mutation that correlates with the functional defect and the presence or absence as well as the half-life of large VWF multimers. Our data emphasize the usefulness of DDAVP testing even in patients with VWD type 2, possibly with the exception of VWD type 2B.
Keywords: Desmopressin; von Willebrand disease